Private equity entities and conglomerates: what are the differences? - Ann-Kristin Achleitner; Kay Müller (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
We compare the characteristics of conglomerates and private equity entities. This is done by examining the differences among their business models. We analyze the relations of the two entity types to their investors on the one hand and to their investments on the other hand. The distinguishing characteristic of private equity entities is that they pursue a stand-alone-perspective with their investment policies, meaning that they treat each investment separately. Therefore, various linkages that exist in conglomerates do not occur in private equity entities. We describe these linkages in detail. We further argue that because of the lack of these linkages in private equity entities the shareholders and debtholders of a private equity entity and its portfolio companies are not faced with the following risks that are specific for a conglomerate: the asset shifting risk, the intra-group profit risk and the capital structure risk. Finally, we define crucial evaluation criteria for identifying a private equity entity and develop a way how regulators and other persons concerned with such a task could do so.
Keywords: G23; G24; G28; 330; private equity; conglomerates; investment companies; Private Equity; Konglomerat; Investmentfonds; Anlageverhalten